THE MODERN METHODS OF COORDINATION IN MANAGEMENT OF UNITED NATIONS COMMUNICATION AND PUBLIC INFORMATION SYSTEM - T. Shchors (Вестник университета)
The article is dedicated to the problems of coordination of United Nations communication and public information system aimed to gain the positive image of the organization throughout the world. The author gives the detailed analyses of the specific of UN communication and public information system, describes the main changes in the result of the UN reform, the main characteristics of new strategic approach to communication, client-orientation approach to the UN public information, the specific of organization of information flow during the communication with internal and external target audiences.